Visualizing photovoltaic nanostructures with high-resolution analytical electron microscopy reveals material phases in bulk heterojunctions - Pfannmöller, Martin; Schröder, Rasmus R. (Synthetic metals, 2012)
The efficiency of bulk heterojunctions (BHJs) depends largely on their 3D morphology at the nanoscale. So far bright-field transmission electron microscopy imaging was used to elucidate their structure, applying imaging conditions, which may compromise reliability of image interpretation. We provide evidence that conventional electron micrographs cannot be used for assessing domain sizes when visualizing BHJs. Instead, we describe an analytical method to distinguish materials by their spectral characteristics, i.e. to visualize a material by its specific electronic excitations. Using analytical microscopy of ultra-thin films combined with optimized data analysis, the electronic excitations can directly be linked to materials and their spatial distribution. This is illustrated for an annealed film of [6,6]-phenyl C61 butyric acid methyl ester and poly(3-hexyl-thiophene), where we create a morphological map of the film based on functional contrast.
Available online 4 October 2011
Gesehen am 14.11.2018